2000
DOI: 10.1073/pnas.97.8.4374
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase is an O 2 sensor in airway chemoreceptors: Evidence from K + current modulation in wild-type and oxidase-deficient mice

Abstract: Pulmonary neuroepithelial bodies (NEBs) are presumed airway chemoreceptors that express the putative O2 sensor protein NADPH oxidase and O 2-sensitive K ؉ channels K ؉ (O2). Although there is a consensus that redox modulation of K ؉ (O2) may be a common O2-sensing mechanism, the identity of the O2 sensor and related coupling pathways are still controversial. To test whether NADPH oxidase is the O 2 sensor in NEB cells, we performed patch-clamp experiments on intact NEBs identified by neutral red staining in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(133 citation statements)
references
References 29 publications
2
129
0
2
Order By: Relevance
“…Intracellular signaling proteins such as NADPH oxidase (34), ryanodine receptor (32), and K ϩ channel (31) can work as redox sensors (33). Our results add G i and G o to the growing members of the redox-sensing protein family.…”
Section: Discussionmentioning
confidence: 66%
“…Intracellular signaling proteins such as NADPH oxidase (34), ryanodine receptor (32), and K ϩ channel (31) can work as redox sensors (33). Our results add G i and G o to the growing members of the redox-sensing protein family.…”
Section: Discussionmentioning
confidence: 66%
“…In the respiratory tract, pulmonary neuroepithelial bodies (NEBs) within the airway mucosa represent specialized pulmonary structures that are composed of clusters of innervated amine-and peptide-containing cells, and are involved in mediating airway responses to hypoxia. Based on studies with NADPH oxidase inhibitors and gp91phox (NOX2)-deficient mice, it has been demonstrated that these responses are due to the presence of NOX2, which acts as an oxygen sensor by regulating O 2 -sensitive K+ currents, via altered production of ROS (4,175). NADPH oxidase (most likely NOX2) has been suggested to play a more universal role as oxygen sensor in various tissues, thereby mediating hypoxic pulmonary vasoconstriction, vascular smooth muscle function, and carotid and airway chemoreceptor activation (4).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…It is interesting to note that the Rac-ROS signaling module has also been implicated in oxygen sensing (Fu et al, 2000), and may therefore have a specific role in directing circulating malignant cells towards the lungs along a chemotactic gradient of pO 2 .…”
Section: Discussionmentioning
confidence: 99%